Separation Process and Microstructure-Chemical Composition Relationship of Cenospheres from Lignite Fly Ash Produced from Coal-Fired Power Plant in Thailand - Yoriya, Sorachon; Tepsri, Phattarathicha (Applied sciences, 2020)
The cenosphere is one becoming a focus of the power plant in terms of value addition and ash management. This study presents a systematic investigation and characterization of physical properties, morphological structures, and chemical composition of cenospheres separated from fly ash produced from the Mae Moh coal-fired power plant, Thailand. To our knowledge, this is the first report on cenospheres separation from Mae Moh class C fly ash, with high calcium content ~24 wt.%, by adopting the traditional wet separation method (using water as the medium) to separate the lightweight cenospheres. Various effects of process parameters (fly ash-to-water ratio, stirring method, ultrasonication, and size classification) were designed to examine the cenosphere recovery yield in comparison. The result has revealed the limit of physical stirring-settling effect associated with the cenospheres content by nature governing the percent recovery. The bulk cenospheres were subject to size sieving into different sized fractions, with the structure-chemical composition relationship established for more insight. The particle diameter/shell thickness ratio revealed its significant correlation with the aluminosilicate glass composition, with the relating cenosphere shell structures (single-ring and porous) mapped to compare for a better elucidation of their structure-property relationship. The phase composition was also studied.